Monday

November 24, 2014

November 24, 2014

Posted by **Randy** on Wednesday, April 25, 2012 at 8:40pm.

h(x)=3 x-1

(a) h(0) =

(b) h(-7) =

**Answer this Question**

**Related Questions**

ALGEBRA - Find the functional values requested in the problem. h(x)=5 x-1

Math - Find the functional values requested in the problem; h(x)=5x-4 (a) h(0...

math - find the functional values requested in the problem F(x)=x^2-25t (a)F(5t...

Math - How will I work this problem? Find the functional values requested in the...

ALGEBRA - Assume f(x) = x2 + 4. Find the functional value requested. f(-3) =

ALGEBRA - Assume f(x) = x2 + 3. Find the functional value requested. f(-7) =

ALGEBRA - Assume f(x) = x2 + 3. Find the functional value requested. f(-7)

Math - Assume f(x) = x2 + 3. Find the functional value requested. f(-5) =

MATH - Assume f(x) = x2 + 4. Find the functional value requested. f(-6) =

algebra - Find the functional values f(-2), f(0), and f(1) for the function. ƒ(x...